Concepts of Citizenship in Eastern and Western Europe - Oltay Edith (Acta Universitatis Sapientiae: European and Regional Studies, 2017)
The classical meaning of citizenship evokes a nation-state with a well-defined territory for its nationals, where national identity and sovereignty play a key role. Global developments are challenging the traditional nation-state and open a new stage in the history of citizenship. Transnational citizenship involving dual and multiple citizenships has become more and more accepted in Europe. Numerous scholars envisaged a post-national development where the nation-state no longer plays a key role. While scholarly research tended to focus on developments in Western Europe, a dynamic development also took place in Eastern Europe following the collapse of communism. Dual citizenship was introduced in most Eastern European countries, but its purpose was to strengthen the nation by giving the ethnic kin abroad citizenship and non-resident voting rights. In Western Europe, the right of migrants to citizenship has been expanded throughout the years in the hope that this would result in their better integration into society. Eastern Europe and Western Europe operate with different concepts of citizenship because of their diverging historical traditions and current concerns. The concept of nation and who belong to the national community play a key role in the type of citizenship that they advocate.